The effect of analytic text-based writing strategies on ESL argumentative writing among Malaysian Form-six students in Sabah, Malaysia - Rosalind Joannes,; Asmaa Alsaqqaf, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Producing effective and high-quality academic writing, such as argumentative writing, requires more than regular writing ability; it demands analytical writing that can increase argumentation skills and promote higher cognitive skills. This study was conducted to address a problem that exists within the Malaysian education setting where English-as-a-second language (ESL) learners face difficulties in presenting and expanding their ideas and viewpoints convincingly, lack of knowledge of the subject matter and inadequate language competence. Therefore, this paper aims to investigate the effect of analytic text-based writing strategies on the students' argumentative performance, proposing a conceptual framework that integrates the approach of text-based instruction and the writing model by Hyland (2003) that emphasises the genre approach of teaching writing. Utilising a mixed-method sequential explanatory research design, the current research employed a quasi-experiment with a convenient sampling to collect the quantitative data from two groups of Form-Six students at a public school in Sabah, Malaysia. The experimental group received a 12-week intervention programme, while the control group continued with their regular classroom practices. A pre-test and a post-test were conducted for both groups before and after the intervention, followed by a semi-structured interview that was carried out with a focus group to elicit students’ responses about their learning experiences. The paired-sample t-test indicated that the student’s writing performance significantly improved from the pre-test (30.27) to the post-test (40.27) with a large effect size (.77). On the other hand, four themes were derived from the students' responses as the following: an efficient way of distinguishing important information, an effective way of organising ideas, useful guide for argumentative essay and enriching students' knowledge. This research recommends more comprehensive explorations of text-based analytic writing to expose its' dynamic effect on students' writing advancement.